Preparation and property test of porous Cu–Sn alloy by powder filling and sintering method. (20th September 2019) - Huang, Ben Sheng; Fu, Sheng; Zhang, Shun Shun; Ju, Chun Yan; Wu, Song Song; Peng, Hao
Abstract: A porous Cu–Sn alloy with good pore formation and uniform distribution can be successfully prepared by filling sintering method with mixed powder of copper powder and tin powder as raw materials and K2 CO3 as pore-forming agent under the conditions of ball milling for 20 min, blank forming pressure of 70 MPa, sintering at 900 °C and heat preservation for 1 h. By SEM, EDS, XRD and universal testing machine, the composition, particle size, microstructure and mechanical properties of porous copper alloy under different ball milling times were studied. The results show that the porosity of porous Cu–Sn alloy sample decreases with the increase of Sn powder content from 0% to 4% (mass fraction, the same below). The pore-forming agent K2 CO3 does not react with Cu powder and Sn powder, which not only contributes to the formation of pores, but also is easy to be treated in later stage. The compressive resistance of porous copper alloy prepared was higher than that of porous pure copper. With the increase of Sn powder content, the curvature of porous copper alloy increases in the elastic stage, and the pressure value corresponding to plastic deformation increases, indicating that its ability to resist plastic deformation increases. However, the strain range has not changed significantly, indicating that the ductility has not changed much.